Tourism in Lisbon : evaluating the marketing impact - Oliveira, Ana Margarida Resende Matos Borges de (2017)
Lisbon became a popular destination among foreign visitors and so the tourism industry has evolved in a significant and positive way during the past years. It evolved into one of the most important industries in Portugal and consequently into one important component of the country’s economy. Turismo de Portugal is the Portuguese organization in charge of promoting Lisbon as a tourism destination. In order to attract more tourists and continue to evolve, the organization felt the need to adapt to nowadays’ reality and define a new strategy when it comes to promote Lisbon to the visitors of the world. The aim of this dissertation is to study Lisbon as a touristic destination and understand its impact on the residents. This dissertation provides an overview of Lisbon’s main features and characteristics as a city as well as the evolution of tourism. The focus of the case study is the new strategic marketing plan for promoting Lisbon as a travel destination, developed by Turismo de Portugal, and it is decomposed in four main parts: objectives, product, markets and promotion. Furthermore, this dissertation addresses the impact of tourism on residents with the analysis of the results of a survey targeting only Lisbon’s residents in order to understand their attitude and perspective towards tourism.